Clinical features of patients with male breast cancer in Shanxi province of China from 2007 to 2016. (27th October 2018) - Wang, Weigang; Xu, Xiaoqin; Tian, Baoguo; Wang, Yan; Du, Lili; Sun, Ting; Shi, Yanchun; Zhao, Xianwen; Jia, Yali; Xi, Yanfeng; Jing, Jiexian
Abstract : This study aims to understand the clinical features, treatment, and prognosis of patients with male breast cancer (MBC) in Shanxi province of China from 2007 to 2016. Data for 77 patients with MBC were collected for analysis. Immunohistochemistry, pathological results, and other data such as demographic characteristics (age, marital status, smoking history, drinking history, and family history of cancer) as well as clinical data were investigated by retrieving information from the patients' medical records. A total of 12, 404 patients were diagnosed with breast cancer between 2007 and 2016, and 77 were patients with MBC among them. The median diagnosis age of patients with MBC was 62 years (range, 24–84 years). The most common complaint was a painless lump in the breast, accounting for 68.8% of the patients, and the main pathological type in MBC was infiltrating ductal carcinoma (66.2%). In terms of hormone receptors, 80.5% (62/77) of patients with MBC were estrogen receptor positive, 75.3% (58/77) of patients were progesterone receptor positive, and only 6.5% (5/77) of patients were HER2 overexpressing. The multivariant Cox proportional hazards regression analysis showed that M stage is an independent prognostic factor (p=0.018, HR=18.791, 95% CI 1.663 to 212.6). The epidemiological and clinical features of Chinese MBC are similar to that of other countries. As the Chinese public have limited knowledge of MBC, it is necessary to increase awareness among them about it. Further research with a large sample size is required for better understanding of the risks associated with MBC.